PERANCANGAN KAPAL IKAN HEMAT ENERGI UNTUK WILAYAH PROVINSI KEPULAUAN RIAU - Firman Apriansyah; Muhd Ridho Baihaque; Fahreza Nur Akbar (JURNAL JALASENA, 2023)
The Riau Islands has 96% ocean and own large potential of capture fisheries resources compare to amount of capture fisheries production which not optimal because increasing fuel oil prices and It fishing gear is not comparable with foreign vessels with modern fishing gear. This study aims to design saving energy fishing vessel including lines plan, general arrangement, and 3D drawings, Analyzing Ship stability and Hydrostatic according to regulation sailing to Riau Islands Province area. This vessel provided by solar panel which can distribute the energy to generator and can saving fuel oil until 4725 liter in 15 days operation with stability calculation and hydrostatic analysis comply with regulation. This vessel can increase capture fisheries production with innovation of renewable energy in this vessel.